Um estudo da aplicação da realidade aumentada projetiva em jogos e sua implementação em um protótipo de jogo de corrida - Oliveira, Fernando Cincinato Alves de (Universidade Federal de São Carlos, 2025)
This study aimed to evaluate the design made by digital game users with augmented reality AR, as well as to understand whether this technique can facilitate the design of digital games. Thus, a prototype of a digital racing game was developed. In this game, participants have drawn racetracks and the image of which was captured with a cell phone camera and transferred to a personal notebook, which, in turn, processed the image so that all participants could participate in a race on that track. Thus, to measure and understand the results of the interaction with augmented reality, semi-structured interviews were conducted with each of the 29 participants, which provided positive evidence that augmented reality could be used for game development.
A study of the application of projective augmented reality in games and its implementation in a racing-game prototype
Keywords: Jogos digitais; Game design; Realidade aumentada; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO; 9. Indústria, Inovação e Infraestrutura